A diffusion tensor MRI study of patients with MCI and AD with a 2-year clinical follow-up - Scola, Elisa; Bozzali, Marco; Agosta, Federica; Magnani, Giuseppe; Franceschi, Massimo; Sormani, Maria Pia; Cercignani, Mara; Pagani, Elisabetta; Falautano, Monica; Filippi, Massimo; Falini, Andrea (Journal of neurology, neurosurgery and psychiatry, 2010)
ObjectiveThe authors assessed whether brain changes detected by diffusion tensor (DT) MRI can improve the understanding of structural damage in Alzheimer's disease (AD) and are associated with different risks of conversion to AD in amnestic mild cognitive impairment (aMCI).MethodsTwenty-one aMCI patients, 21 AD patients and 20 healthy subjects underwent conventional and DT MRI at baseline. All subjects were clinically followed up over 2 years; at the end of follow-up, aMCI were grouped into converters to AD (aMCI-C) and non-converters (aMCI-NC). The mean diffusivity (MD) and fractional anisotropy (FA) were obtained from total grey matter (GM) and white matter (WM), and from several GM and WM regions of interest (ROIs). On T1-weighted images, normalised volumes of the whole brain (NBV), GM (NGMV) and WM were measured.ResultsA significant ‘trend’ of worsening with a trajectory ‘normal/aMCI/AD’ was found for NBV and NGMV, total GM and WM MD, total WM FA, as well as for diffusivity abnormalities in several GM and WM ROIs, mainly located in posterior brain regions. aMCI-C had GM and WM changes similar to those seen in AD, whereas aMCI-NC showed a DT MRI pattern similar to that of healthy subjects. DT MRI metrics that better distinguished aMCI-C from aMCI-NC were MD of total GM and WM, hippocampi, anterior insulae, frontal and parietal WM, occipital GM and WM, and FA of temporal WM. Volumetric variables were not able to distinguish the two aMCI subgroups (aMCI-C and aMCI-NC).ConclusionsSubtle brain diffusivity changes occur from the prodromal stages of AD, mainly in posterior brain regions, and spread over the course of the disease to involve the frontal lobe. In aMCI, the severity of microstructural damage within and beyond the medial temporal lobe is associated with an increased short-term risk to develop AD.